1999
DOI: 10.1105/tpc.11.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Two Maize cDNAs Encoding T7-like RNA Polymerases

Abstract: We have characterized two maize cDNAs, rpoTm and rpoTp, that encode putative T7-like RNA polymerases. In vivo cellular localization experiments using transient expression of the green fluorescent protein suggest that their encoded proteins are targeted exclusively to mitochondria and plastids, respectively. An antibody raised against the C terminus of the rpoTp gene product identified mitochondrial polypeptides of approximately 100 kD. Their presence was correlated with RNA polymerase activity, and the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 69 publications
(93 reference statements)
3
76
0
Order By: Relevance
“…psort.org/). Subcellular localization analyses using transient expression of green fluorescent protein (GFP)-related constructs, such as, the AtHIRP1-GFP expression construct, the GFP expression construct (Chiu et al 1996;Niwa 2003), the plastid-targeting GFP expression construct (Engprasert et al 2004), and the mitochondriatargeting GFP expression construct (Chang et al 1999) in onion (Allium cepa) epidermal cells suggest that AtHIRP1 is likely distributed in the plastids (Supplemental data 3).…”
Section: ϩmentioning
confidence: 99%
“…psort.org/). Subcellular localization analyses using transient expression of green fluorescent protein (GFP)-related constructs, such as, the AtHIRP1-GFP expression construct, the GFP expression construct (Chiu et al 1996;Niwa 2003), the plastid-targeting GFP expression construct (Engprasert et al 2004), and the mitochondriatargeting GFP expression construct (Chang et al 1999) in onion (Allium cepa) epidermal cells suggest that AtHIRP1 is likely distributed in the plastids (Supplemental data 3).…”
Section: ϩmentioning
confidence: 99%
“…As controls to demonstrate chloroplast and mitochondrial targeting patterns, GFP was fused to the chloroplast transit peptide sequence of Rubisco small subunit or to the mitochondrial targeting sequence of the F 0 F 1 ATPase ␥-subunit (Chang et al, 1999;Beardslee et al, 2002). Strong GFP fluorescence (Fig.…”
Section: Atsig5 Nh 2 Termini Initiating At M1 or M2 Are Targeted To Dmentioning
confidence: 99%
“…The inserts were sequenced to verify the insert orientation and the lack of PCR-based sequence errors. All control GFP vectors and transient assay protocols with leaf protoplasts were described previously (Chang et al, 1999;Beardslee et al, 2002). For transient assays in intact Arabidopsis leaf tissues, rosette leaves of 10-d-old greenhouse-grown seedlings (Columbia ecotype) were excised and arranged abaxial side up in a filled circle pattern on hormone-free Murashige and Skoog medium (Murashige and Skoog, 1962).…”
Section: Subcellular Localization Of Transiently Expressed Atsig5-gfpmentioning
confidence: 99%
“…5 and 6). However, only two genes (RPOTp and RPOTm) have been detected in monocotyledons (4,7,8), thus raising the question of the function of RPOTmp in plastids of dicotyledon plants. Recent results have shown that RPOTp can be regarded as the principal NEP enzyme in chloroplasts playing an important role in chloroplast transcription, biogenesis, and mesophyll cell proliferation (9,10).…”
mentioning
confidence: 99%
“…One of the three RNA polymerases is of the eubacterial type, and its subunits are encoded on the plastid genome [plastid-encoded RNA polymerase (PEP)]. The two other RNA polymerases are nucleus-encoded [nucleus encoded plastid RNA polymerase (NEP)] and of the phage type (3,4). Three different genes have been identified in Arabidopsis coding for NEP proteins that are localized in mitochondria (RPOTm, At1g68990), plastids (RPOTp, At2g24120), or in both organelles (RPOTmp, At5g15700; refs.…”
mentioning
confidence: 99%